1992
DOI: 10.1002/maco.19920430703
|View full text |Cite
|
Sign up to set email alerts
|

Zum Einfluß eines wäßrigen Mediums auf die Simulation von Erosion und Erosionskorrosion

Abstract: Die Untersuchung der Rolle eines Mediums bei erosiv-korrosiver Beanspruchung erfordert, dal3 die mechanische Kornponente der Beanspruchung bei erosiver und bei erosiv-korrosiver Arbeitsweise vergleichbar bleibt. Einige Experimente gaben jedoch Hinweise darauf, daB die Zugabe waBriger Medien zum Teilchenstrahl zu Veranderungen des Beanspruchungsregimes fiihrt.Mit der vorliegenden Arbeit wird die Medieneinwirkung auf den Abwurfwinkel, die Strahlgeometrie und Partikelverteilung und den Auftreffimpuls mit verschie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…It can thus be concluded that at elevated temperatures, after a given running-in sliding distance, needed for covering the surface with transferred ball material, the COF is predominately defined by the tribo-system of ball against ball material transferred to the coating. The rising ball wear with increasing temperatures can be attributed to an accompanied softening of the austenite and martensite phases, where the latter are known to be formed in dry sliding contacts due to austentite/martensite transformation [25][26][27][28].…”
Section: Discussionmentioning
confidence: 98%
“…It can thus be concluded that at elevated temperatures, after a given running-in sliding distance, needed for covering the surface with transferred ball material, the COF is predominately defined by the tribo-system of ball against ball material transferred to the coating. The rising ball wear with increasing temperatures can be attributed to an accompanied softening of the austenite and martensite phases, where the latter are known to be formed in dry sliding contacts due to austentite/martensite transformation [25][26][27][28].…”
Section: Discussionmentioning
confidence: 98%